The Role of Lipids in the Initiation of α-Synuclein Misfolding - Kiechle, Martin; Grozdanov, Veselin; Danzer, Karin M. (Frontiers in Cell and Developmental Biology, 2020)
The aggregation of α-synuclein (α-syn) is inseparably connected to Parkinson’s disease (PD). It is now well-established that certain forms of α-syn aggregates, oligomers and fibrils, can exert neurotoxicity in synucleinopathies. With the exception of rare familial forms, the vast majority of PD cases are idiopathic. Understanding the earliest molecular mechanisms that cause initial α-syn misfolding could help to explain why PD affects only some individuals and others not. Factors that chaperone the transition of α-syn’s physiological to pathological function are of particular interest, since they offer opportunities for intervention. The relationship between α-syn and lipids represents one of those factors. Membrane interaction is crucial for normal cellular function, but lipids also induce the aggregation of α-syn, causing cell toxicity. Also, disease-causing or risk-factor mutations in genes related to lipid metabolism like PLA2G6, SCARB2 or GBA1 highlight the close connection of PD and lipids. Despite the clear link, the ambivalent interaction has so far not been studied sufficiently. In this review, we address how α-syn interacts with lipids and how they can act as key factor for orchestrating toxic conversion of α-syn. Furthermore, we will discuss a scenario in which initial α-syn aggregation is determined by shifts in lipid/α-syn ratio as well as by dyshomeostasis of membrane bound/unbound state of α-syn.